Hubunagn kemampuan pergantian inang dengan plastisitas genetika pada cendawan blas padi (Pyricularia grisea) - Sri Listiyowati; Utut Widyastuti; Gayuh Rahayu; Alex Hartana; Muhammad Jusuf (Institut Pertanian Bogor, 2009)
The Digitaria ciliaris, wild grass grown around rice field, was a host for Pyricularia grisea (Cooke) Sacc., the fungi caused blast disease of rice. This fungi have a specific mechanism to regenerate new genetic variation in its life cycle. The aim of this research is to study the relation between the ability of the fungi to infect different species of host with its genetic plasticity. It was used three SCAR molecular markers Cutl, Pwl 1 and Erg2. P. grisea isolates (Dc4J1) originated from D. ciliaris at Jasinga-Bogor were able to infect rice cultivars Kencana Bali and Cisokan. The original Dc4Jl, from D. ciliaris, and the Dc4Jl that were reisolated from the infected rice cultivars (reisolates-1) had the same ability to infect Kencana Bali and Cisokan. Molecular technique showed that there was a different molecular marker genotype between the original Dc4J1, from D. ciliaris, and the Dc4Jl reisolated from infected rice cultivars. The original Dc4J1 owned Cutl but did not Pwl2 in contrary the reisolates Dc4J1 from rice cultivars (reisolates-1) had Pwl2 but did not Cutl. The Erg2 presented in both the original and the reisolated Dc4Jl. These results indicated that there were a change of genotype of P. grisea at the same time with the change of host species. The Dc4Jl isolates originated from Kencana Bali and Cisokan (reisolates-2) that were infected by reisolate-1, had the same genotype with the reisolates-1.